“GUIDELINES FOR DESIGNING EFFECTIVE LANGUAGE TEACHING MATERIALS - Rustamov Ilkhom Tursunovich (American Journals Publishing, 2022)
This article investigates the problem of developing guidelines, manuals for effective teaching aids in teaching a foreign language to students in order to form foreign language communicative competencies. Moreover, the article discusses the requirements that must be observed when creating effective teaching aids. On the example of the educational and methodological several manuals, the main principles and parameters that teachers should be taken into account in the process of writing teaching aids due to the transition to new educational standards. The educational and methodological manuals are the result of productive and systematic work, which required time, as well as the cooperation of teachers, methodologists and specialists in the field of information and communication technologies. In the article, the educational and methodological manual is of a complex nature, since it offers tasks for practicing and improving all types of speech activity: reading, listening, speaking and writing.
Keywords: linguistic competence, communicative competence, intercultural communication, vocabulary, grammar exercises, case method, reading, speaking, listening, writing, types of speech activity, interactive technology.